College matriculation : Physics semester 2 - Zainal Abidin Sulaiman; Siti Hendon Sheikh Abdullah; Saifful Kamaluddin Muzakir; Halimah Mohamed Kamari; Zalita Zainuddin (Selangor : SAP Publications Sdn. Bhd., 2011)
PSZJBL